Integrating Human Behavior and Safety Measure into Evacuation Route Planning in a Volcanic Crisis - Wibowo, Budhi; Hartono, Budi (Institute of Research and Community Outreach - Petra Christian University, 2020)
Many traditional methods in evacuation route planning are motivated by the operational objective, such as total travel/clearance time. Little attention has been given to the human factor and the safety aspect of the evacuees during the planning phase. Our study aims to propose a simple yet practical route planning method that simultaneously considers human behavior, safety factor, and the travel time in a volcanic crisis context. The planning model is developed based on the shortest-path problem with a joint-cost parameter representing the three aspects. We present a large-scale street network in Merapi volcano as a case study. The result implies that employing a joint-cost parameter is effective for creating an evacuation route that is reasonably safe and in line with human cognition in navigation. The finding offers practical insights for the stakeholders as part of the greater effort to develop a systematic disaster management plan.